A Comparative and Interdisciplinary Analysis of the Concept of Responsibility in Viktor Frankl's Theory of Logotherapy and Rumi's Masnavi - Shabnam Ghadiri Yeganeh; Esmail Azar; Sareh Zirak (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
The current research is a comparative and interdisciplinary analysis of the concept of responsibility in Austrian psychiatrist, Viktor Frankl’s theory of logotherapy, and Rumi, a famous Iranian poet and mystic. In Logotherapy, freedom of will and responsibility are intertwined and indicative of humanity. According to Frankl, recognizing one's responsibility is one way to discover the meaning of life. Rumi also considers responsibility as the foundation of life and guides people to act responsibly in this world and for the hereafter. Similar to Frankl, he considers us responsible to God, ourselves, others, in situations and in our destiny and warns against projection. The present research draws on a descriptive-analytical method to compare and contrast the views of these two thinkers on the concept of responsibility. In other words, the paper is a comparative study of a prominent psychological theory with Rumi's mystical-educational views. The results of the research show that the sources from which the same doctrine initiates in these two thinkers are different. Frankl deals with the concept of responsibility from the stand point of existentialist psychology, and Rumi does so, from the perspective of Quranic teachings and Islamic mysticism. Frankel believes in discovering a unique responsibility in regard to all aspects of life. Rumi, on the other hand, believes in each person’s specific responsibilities as well as fundamental human responsibilities. According to Frankl, every human being is responsible for his/her choices in this world; however, in Rumi's view, one's responsibility for his/her actions is not limited to the life in this world; one's actions determine one's state of reward and punishment in the afterlife. Frankel considers evasion of responsibility as a result of the inability to discover meaning, while Rumi considers it as a result of the mastery of carnal desires and a root cause many immoralities.